CGP 55845A blocks baclofen, γ-aminobutyric acid and inhibitory postsynaptic potassium currents in guinea pig CA3 neurons - Jarolimek, Wolfgang; Demmelhuber, J.; Bijak, Maria; Misgeld, Ulrich (Neuroscience letters, 1993)
Single electrode voltage-clamp recording from CA3 neurons in guinea pig hippocampal slices was applied to study effects of a new GABAB antagonist, CGP 55845A, on (−)baclofen (IBac)- or γ-aminobutyric acid (IGABA)-induced potassium (K)-currents and on inhibitory postsynaptic K-currents (K-IPSCs) recorded in the presence of blockers for fast synaptic transmission. K-IPSCs were induced by bath application of 4-aminopyridine (4-AP). CGP 55845A, in 10−8 to 10−7 M concentrations, blocked all these K-currents and was more potent than all GABAB antagonists known to date. However, onset of the CGP 55845A effect and recovery were slow. We conclude that a potent and selective GABAB antagonist is now available to study the physiological role of GABAB receptors in the mammalian brain.
Online 24 March 2003
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 08.04.2021